Muligheder for samarbejde mellem ordbøger der arbejder inden for det nordiske sprogområde - Jacobsen, Bent Christian (Nordiske Studier i Leksikografi, 2006)
Plans for co-operation between Nordic-language dictionary projects. The West-Nordic language area covers Norway, the Faeroes and Iceland. The languages of these three countries all develop from a common source, usually called Old Norse (Danish: ‘norrønt’). The article describes the way in which dictionaries of the modern forms of these languages can benefit from being able to refer to corresponding words both in the sister languages and in Old Norse. Ordbog over det norrøne prosasprog // A Dictionary of Old Norse Prose makes considerable use of lexicographical material from related medieval and modern languages when undertaking semantic analysis. An initiative is under way to enable dictionary projects that cover all medieval Nordic languages to co-operate on an interlinked presentation of their lexical data and some background materials on the World Wide Web.